Health promotion for young family farmers: perspective for healthy aging - Ângela Urio; Jeane Barros de Souza; Daniela Savi Geremia; Ivonete Teresinha S. Buss Heidemann; Liane Colliselli (Universidade Federal de Santa Maria, 2020)
Objective: to understand how young farmers take care of their health in the face of vulnerabilities in the work context, thereby unveiling their perspectives for a healthy aging. Method: exploratory, descriptive and qualitative research, performed with ten young people from a town in Rio Grande do Sul, held in the second half of 2018. Data collection took place through semi-structured interviews. Data analysis was based on content analysis. Results: young people promote their health by taking care of food, water intake, climatic adaptations, leisure and maintenance of family relationships. For healthy aging, research participants seek the introduction of technologies focused on relieving physical effort and adhering to preventive practices, showing hereditary concerns and comorbidities. Conclusion: health promotion is held from the care with food, water intake, adaptations to the climate and good family relationships. Physical exercises are not practiced because work activities require intense physical effort.